Decoupling China’s mining carbon emissions from economic development: Analysis of influencing factors - Sun, Wenjie; Ren, Shunli; Liu, Kai; Zan, Chaoyao (Frontiers in Environmental Science, 2022)
Mining provides basic material and energy to human’s life and production, and supports economic and social prosperity and development. The relative decoupling of mining carbon emissions from economic development is an important way to realize China's carbon peaking and carbon neutrality goals. This paper uses Tapio decoupling model to measure the relationship between China's economic development and carbon emission from 2001 to 2018 based on the overall and single industry, analyzes the decoupling state between China's mining carbon emissions and economic growth, and decomposes the driving factors of mining carbon emission in combination with the improved Kaya identity and LMDI decomposition model, The results show that: ①Except for the unstable development of the oil and natural gas mining industry, the other mining industries have reached and stabilized in a state of strong decoupling, showing a continuous positive trend; ②On the whole, The mining product smelting and processing industry has achieved a major transformation from negative decoupling to weak decoupling, but there are great differences between different sub-sectors; ③The overall consumption of China's mining products and the increment of carbon emission have continued to decline, and the economic development has shifted from inefficient expansion to high-quality economic development, but it has not reached the ideal state;④The economic factor effect and the energy intensity effect are the key factors to increase and restrain carbon emissions respectively, but their influence should not be ignored. This study aims to provide decision-making basis for China's mining industry to carry out carbon emission reduction planning, and promote the clean and efficient construction of the mining industry and the green and high-quality development of the economy.